Distribution of wild potato species in the north of the Deparment of La Paz, Bolivia - Coca Morante, M.=700 1 Ticona, V.H.; Castillo Plata, W.; Tolin Tordoya, I.
(En, Es)
Ilus., 10 ref.
Keywords: SOLANUM TUBEROSUM; ESPECIES EN PELIGRO DE EXTINCION<<PHYTOPHTHORA INFESTANS; BOLIVIA; ESPECIES SILVESTRES